Effects of oestrogen deprivation on interleukin-6 production by peripheral blood mononuclear cells of postmenopausal women. - Rachoń, D; Myśliwska, J; Suchecka-Rachoń, K; Wieckiewicz, J; Myśliwski, A (2002)
Various hormones can influence the expression of interleukin-6 (IL-6) and oestrogens are the most extensively studied. There is, however, controversy about the nature of the IL-6 secreted by human cells and its regulation by 17beta-oestradiol. The aim of this work was to clarify whether oestrogen deprivation after menopause may contribute to an enhanced IL-6 production by peripheral blood mononuclear cells (PBMC) in postmenopausal women. Twenty-two healthy postmenopausal women, age range 45-63 years, with clinical symptoms of oestrogen deficiency were enrolled in the study. The control group consisted of 16 healthy young women, age range 22-31 years, with regular menses and who were not taking oral contraceptives. Levels of IL-6 in the sera and PBMC culture supernatants were measured by the biological B9 cell-proliferation assay and expression of the IL-6 gene in non-stimulated PBMC was detected by RT-PCR. The effect of 17beta-oestradiol on spontaneous IL-6 production by the PBMC of postmenopausal women was also studied in vitro and in vivo. Seventeen out of the twenty-two postmenopausal women were given hormonal replacement therapy of 50 microg 17beta-oestradiol/day transdermally and the spontaneous production of IL-6 by the PBMC was analysed after 6 and 12 months of treatment. The postmenopausal women had significantly higher serum levels of IL-6 than the young controls. The spontaneous production of IL-6 by non-stimulated PBMC into the culture supernatants was also significantly higher in the postmenopausal women compared with the young. We also found that IL-6 gene expression was present in the non-stimulated PBMC isolated directly from the venous blood of the majority of the postmenopausal women. Women with IL-6 gene expression in the non-stimulated PBMC had significantly lower serum levels of 17beta-oestradiol compared with those where the IL-6 gene was not expressed in the PBMC. Our in vitro experiments showed that 17beta-oestradiol at concentrations of 10(-9) M and 10(-10) M decreased spontaneous IL-6 production by the PBMC of postmenopausal women. In vivo treatment with 17beta-oestradiol transdermally also significantly decreased spontaneous IL-6 production by the PBMC of postmenopausal women after 12 months of the therapy. Our results indicate that oestrogen deprivation after menopause may enhance IL-6 production by the PBMC of postmenopausal women. We suspect that the late complications of oestrogen deficiency, such as osteoporosis, coronary heart disease and Alzheimer's disease, may be mediated by an exaggerated production of IL-6 - a cytokine which seems to play a pivotal role in the pathogenesis of these age-related diseases.